Optimization strategy for all-male Nile tilapia (Oreochromis niloticus) production using hormonal complex-microencapsulated feed under different rearing conditions - Natthapong Paankhao; Noratat Prachom; Chak Aranyakanont; Wirawan Nuchchanart; Attawit Kovitvadhi; Chayanit Soontara; Suwinai Paankhao; Kittipong Promsee; Sahat Ratmuangkhwang; Chanoknan Sintuprom; Mongkhon Jaroenkittaweewong; Akkarasiri Sangsawang (Aquaculture Reports)
Optimization strategies were investigated for the production of all-male tilapia (Oreochromis niloticus) fry using a hormone-microencapsulated prototype under different rearing conditions. The factorial design experiment (2 × 2 × 4) used a completely randomized design (CRD) with three factors: two experimental diets (fish meal mixed with rice bran and a complex microcapsule formula); the period of feeding containing the hormone 17α-methyltestosterone (MT) using two periods (14 and 21 days); and the MT hormone concentration at four levels in the mixed diet (0, 10, 30, or 60 mg/kg feed). The experiment had three replicates, with tilapia reared in tanks or reared in hapas nets for a period of 28 days. The results showed that all three factors combined influenced the survival rate of fish fry. The fry fed with both formulas mixed with hormones at concentrations of 10, 30, and 60 mg/kg for 14 and 21 days consisted of more than 95 % males and had the highest mean ± standard deviation survival rate (93.8 ± 5.02 %). The hormone treatment period did not affect the proportion of sex reversion in Nile tilapia fry, while the MT concentration level did affect the sex reversion in Nile tilapia fry to male. The fry reared on the complex-microcapsules feed had better growth than the fry fed the control formula in both tanks and hapas nets. The hormone dose and treatment period significantly affected the relative expression of the cyp19a1a or dmrt1 genes of the fry reared in fiber tanks for 28 days (P < 0.05). Therefore, a feed formula for rearing tilapia larvae at the weaning stage based on the prototype complex hormone-microcapsule feed could be used in place of fish meal to improve the production efficiency of all-male tilapia and reduce the amounts of hormones used in the feed.